SETTLEMENT OF DIFFERENCE IN INDUSTRIAL RELATIONSHIP IN COURT BASED ON LAW NO. 2 YEAR 2004 - OTOM MUSTOMI; DR. HAMDAN AZHAR SIREGAR; DR. TRY WIDIYONO; DR. ABUSTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Labor Dispute Settlement in the Industrial Relations Court Based on Law No. 2 of 2004 concerning the IRC which includes First: Research Objectives To find out and analyze the types of Disputes that can be resolved at the Industrial Relations Court, To find out the position of the Industrial Relations Court in the Judicial System in Indonesia, To find out the Process of Settling Industrial Relations Disputes in the Relations Court Industrial. Second The scope of the research describes the state of labor disputes, the legal protection of the labor justice system. The third research method is to use qualitative research methods that are nominally. The fourth discussion on Settlement of Labor Disputes at the Industrial Relations Court, is regulated by Law No. 48 of 2009 concerning Judicial Power, which also applies to all judicial bodies in the territory of the Republic of Indonesia. Before the enactment of Law No. 2 of 2004 concerning Settlement of Industrial Relations Disputes. Before these steps are taken, they must first be completed through a Bipartite settlement, Conciliation, Mediation, Negotiation and Arbitration, which must be taken first based on an agreement between the worker and the employer. that the existence and entry into force of Law No. 2 of 2004 is a gateway to labor law towards a labor justice system that is fast, accurate, fair and inexpensive and can guarantee legal certainty that is highly coveted by workers and employers in particular and the Indonesian people in general. The Fifth Conclusions in Settling Industrial Relations Disputes there are 4 (four) types of disputes which then become the absolute authority of the Industrial Relations Court, including: First, Rights Disputes. Second, disputes of interest. Third, Work Termination Disputes. Fourth, disputes between trade unions / labor unions. In addition to the settlement process at the Industrial Relations Court, the Industrial Relations Dispute Settlement Act also regulates alternative industrial relations settlements carried out outside the court, namely through bipartite efforts which constitute mandatory, mediation and conciliation efforts which are mandatory effort choices before entering the Industrial Relations Court, and arbitration which is a settlement institution that has a decision of permanent legal force.